2017
DOI: 10.1002/hep.29072
|View full text |Cite
|
Sign up to set email alerts
|

Activation of silent mating type information regulation 2 homolog 1 by human chorionic gonadotropin exerts a therapeutic effect on hepatic injury and inflammation

Abstract: Here, we report that hCG regulates the SIRT1/FOXO3a axis in hepatocytes, resulting in immune suppression by attenuating caspase-3-dependent IL-16 processing and release, which concomitantly prevents autoaggressive T-cell infiltration of the liver. Considering the low toxicity profile of hCG in humans, interrupting the inflammatory cycle by hCG opens new perspectives for therapeutic intervention of inflammatory liver diseases. (Hepatology 2017;65:2074-2089).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Silent information regulator 2 homolog1 (SIRT1), a NAD-dependent histone deacetylase, is involved in the pathogenesis of cancer [ 24 ], metabolic disease [ 25 ], inflammation [ 26 ] and arthritis [ 27 ]. The roles of SIRT1 in RA are mainly focused on the immune response [ 4 6 ], the proliferation and adhesion of RA FLSs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silent information regulator 2 homolog1 (SIRT1), a NAD-dependent histone deacetylase, is involved in the pathogenesis of cancer [ 24 ], metabolic disease [ 25 ], inflammation [ 26 ] and arthritis [ 27 ]. The roles of SIRT1 in RA are mainly focused on the immune response [ 4 6 ], the proliferation and adhesion of RA FLSs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“… 701 Interestingly, pregnancy induces a state of immune tolerance, which can lead to spontaneous improvement of clinical symptoms of autoimmune hepatitis. 702 As for mechanism, this may be associated with the activation of SIRT1 by chorionic gonadotropin signaling. 702 Moreover, SIRT1, SIRT3, and SIRT6 may play important roles in cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“… 702 As for mechanism, this may be associated with the activation of SIRT1 by chorionic gonadotropin signaling. 702 Moreover, SIRT1, SIRT3, and SIRT6 may play important roles in cirrhosis. 665 , 669 , 703 The study suggested that SIRT1 and SIRT6 were decreased at protein level in the livers of patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…BALB/c mice with acute liver injury induced by anti-Fas antibody (Jo 2) and agonistic CD95-antibodieshad significantly reduced levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) when also treated with hCG. Mice treated with hCG also showed less CD4 + T cell infiltration and fewer apoptotic hepatocytes, confirming the effectiveness of hCG as an anti-inflammatory agent (90).…”
Section: Tempering Inflammation With Hcgmentioning
confidence: 60%